2022
DOI: 10.4309/jgi.2022.49.8
|View full text |Cite
|
Sign up to set email alerts
|

Understanding sports betting among young male student-teachers in Ghana

Abstract: Drawing on sports betting, leisure studies and rationality concept provides information to understand how those training to be teachers are gradually gravitating towards gambling to the detriment of their studies at the university. A thorough analysis of 42 young male adults interviewed at betting shops in the university community revealed how they have become involved in sports betting activities for additional financial rewards. Results show that peer pressure is a strong persuader drawing new student teache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Specifically, studies in Ghana have found gambling linked to financial stress (losing money, people incurring debts they are unable to repay, stealing to stake bets), poor mental health and wellbeing (depression, mental instability, sleepless nights), poor academic performance and challenges with personal and social life including family breakdown and crime. 16,18 Why is publiC health aCtion uRgently needed? a comprehensive public health approach to gambling and its harms is vital and has been framed as twofold.…”
Section: Who Is At Risk and What Are The Impacts?mentioning
confidence: 99%
“…Specifically, studies in Ghana have found gambling linked to financial stress (losing money, people incurring debts they are unable to repay, stealing to stake bets), poor mental health and wellbeing (depression, mental instability, sleepless nights), poor academic performance and challenges with personal and social life including family breakdown and crime. 16,18 Why is publiC health aCtion uRgently needed? a comprehensive public health approach to gambling and its harms is vital and has been framed as twofold.…”
Section: Who Is At Risk and What Are The Impacts?mentioning
confidence: 99%
“…The youth, especially those in school constitute about 57.00% of the population of Ghana according to the 2021 population census (Ghana Statistical Service, 2021). Out of the percentage, experts have estimated that twothirds engage in online sports betting from senior high schools to other higher educational institutions (Acheampong et al, 2022). Although the actual percentages of university students who are addicted to online sports betting are not readily available, experts in the field strongly believed the number of university students who are addicted to online sports betting is endemic.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, it is a growing public health concern globally [2][3][4]. The advent of internet gambling and easy access to mobile phones and televisions have made gambling easy [5], with more youth of the working age group getting involved [5][6][7][8][9]. It is legal to engage in online sports betting in Ghana according to the Gaming Act of 2006.…”
Section: Introductionmentioning
confidence: 99%